Respuesta :

Answer:

[tex]2i\sqrt{3}[/tex]

[tex]-2i\sqrt{3}[/tex]

Step-by-step explanation:

[tex]x^2 + 12[/tex]

First set the equation to 0

[tex]x^2 + 12[/tex]

[tex]x^2 + 12 = 0[/tex]

Second, get the 12 on the right side of the equal sign by adding a -12 to each side

[tex]x^2 + 12 = 0[/tex]

[tex]x^2 + 12 + (-12) = 0 -12[/tex]

[tex]x^2 = -12[/tex]

Square root both sides of the equal sign.

[tex]x^2 = -12[/tex]

[tex]\sqrt{x^2} = \sqrt{-12}[/tex]

Take the square root on left sides of the equal sign.

[tex]\sqrt{x^2} = \sqrt{-12}[/tex]

[tex]x = \sqrt{-12}[/tex]

Take the square root on the right side of the equal sign. Remember [tex]\sqrt{-1} = i[/tex]

[tex]x = \sqrt{-12}[/tex]

[tex]x = \sqrt{4}*\sqrt{-1}\sqrt{3}}[/tex]

[tex]x = 2i\sqrt{3}[/tex]

AND

[tex]x = -2i\sqrt{3}[/tex]